EFFECTS OF RESISTANCE TRAINING ON INDICATORS OF NORMAL RESPIRATORY MUSCLE STRENGTH IN ELDERLY (Fiep Bulletin - online, 2013)
Regular practice of resistance exercise is an important to the maintenance of the physical abilities that contribute to improving the quality of life in human. Among the different age groups that benefit from these practices that is situated from 60 years of age, particularly when correlations are established with the force development as predictive indicator of health. The study aimed to compare the effect of resistance exercise and sedentary lifestyle indicator of normal respiratory muscle strength in the elderly of both genders. Character of field research was observational and cross-sectional quantitative. The sample consisted of 19 elderly practitioners of resistance training, 13 women and 6 men and another group consisting of 20 sedentary elderly people of the community, 13 women and 7 men. The purpose was to analyze the respiratory muscle strength by maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP), used a manometer. The normal values ??of (MIP) and (MEP) were determined by Neder (1999). The analysis was performed by descriptive statistical methods. The results obtained from men MIP and MEP of trills than expected in 21.3% and 18.5% respectively and MIP and MEP sedentary lower than expected in 15.3% and 15.9% respectively. Older women who trained with resistance exercises had improved by 6.3% expected MIP and MEP% and 17% among sedentary elderly women had reduced MIP expected at 17.2% and 10.1% expected MEP. We conclude that resistance exercises promote positive adaptations in the development of normal levels of respiratory muscle strength in the elderly, when verified by manovacuometry, contrasting the sedentary lifestyle that promotes negative adaptations.
Keywords: Respiratory Muscles; Elderly; Resistance Training.